Phylogenetic reassessment of tribe Anemoneae (Ranunculaceae): Non-monophyly of Anemone s.l. revealed by plastid datasets. - Nan Jiang; Zhuang Zhou; Jun-Bo Yang; Shu-Dong Zhang; Kai-Yun Guan; Yun-Hong Tan; Wen-Bin Yu (PLoS ONE, 2017)
Morphological and molecular evidence strongly supported the monophyly of tribe Anemoneae DC.; however, phylogenetic relationships among genera of this tribe have still not been fully resolved. In this study, we sampled 120 specimens representing 82 taxa of tribe Anemoneae. One nuclear ribosomal internal transcribed spacer (nrITS) and six plastid markers (atpB-rbcL, matK, psbA-trnQ, rpoB-trnC, rbcL and rps16) were amplified and sequenced. Both Maximum likelihood and Bayesian inference methods were used to reconstruct phylogenies for this tribe. Individual datasets supported all traditional genera as monophyletic, except Anemone and Clematis that were polyphyletic and paraphyletic, respectively, and revealed that the seven single-gene datasets can be split into two groups, i.e. nrITS + atpB-rbcL and the remaining five plastid markers. The combined nrITS + atpB-rbcL dataset recovered monophyly of subtribes Anemoninae (i.e. Anemone s.l.) and Clematidinae (including Anemoclema), respectively. However, the concatenated plastid dataset showed that one group of subtribes Anemoninae (Hepatica and Anemone spp. from subgenus Anemonidium) close to the clade Clematis s.l. + Anemoclema. Our results strongly supported a close relationship between Anemoclema and Clematis s.l., which included Archiclematis and Naravelia. Non-monophyly of Anemone s.l. using the plastid dataset indicates to revise as two genera, new Anemone s.l. (including Pulsatilla, Barneoudia, Oreithales and Knowltonia), Hepatica (corresponding to Anemone subgenus Anemonidium).